Biomechanical analysis of narrow dental implants for maxillary anterior rehabilitation - Santinoni, Carolina Dos Santos; Batista, Victor Eduardo de Souza [UNESP]; Oliveira, Hiskell Francine Fernandes e [UNESP]; Lemos, Cleidiel Aparecido Araújo; Cruz, Ronaldo Silva [UNESP]; Verri, Fellippo Ramos [UNESP] (FapUNIFESP (SciELO), 2023)
Introduction: Narrow diameter implants biomechanics knowledge indicates safe dimensions for clinical use. Objective: Purpose of the present study was biomechanically to compare regular and narrow diameter implants to support single implant-supported prosthesis in the anterior region of the maxilla by 3D finite element analysis (3D-FEA). Material and method: Four 3D-FEA models were developed form CT scan recompositing and literature data: a bone block in the right upper lateral incisive region with implant and crown. M1: 3.75 x 13 mm, M2: 3.75 x 8.5 mm, M3: 2.9 x 13 mm and M4: 2.9 x 8.5 mm. It was applied load was of 178 N at 0, 30 and 60 degrees in relation to implant long axis. Von Mises stress, maximum principal stress and microdeformation maps were evaluated. Result: M3 and M4 did show higher tension and higher microdeformation values than M1 and M2, especially when inclined forces were applied. However, M3 presented enhanced biomechanical behavior than M4. Conclusion: It can be concluded that reduce the diameter of the implants can disadvantage to the biomechanics during the application of forces, but the distribution and intensity of the stresses, as well as the micro deformation values can be improved if the length of the implant is increased.
Análise biomecânica de implantes de diâmetro reduzido para reabilitação da região anterior da maxila
Keywords: bone; Dental implantation; finite element analysis; stress, mechanical